Relationship between gut microbiota and mood disorders and the influence that nutrition can exert on this mechanism: A systematic review (Research, Society and Development, 2022)
Objective: This work seeks to analyze the relationship between the intestinal microbiota and the development of psychological pathologies. Methodology: Systematic review, carried out between February 2020 and March 2021. To develop the theoretical framework, a selection of articles was carried out through the search platforms PubMed, Science Direct, Scielo and Lilacs. Results: Experimental studies demonstrate that the intestinal microbiota interferes with the behavior of the host both through the synthesis of neuroactive substances such as serotonin, dopamine and gamma-aminobutyric acid, attenuating behaviors related to anxiety and stress, as well as through the regulation of the Hypothalamus- Pituitary-Adrenal, being the imbalance of the intestinal flora responsible for its hyperactivity, with consequent promotion of more anxious and stressed behavior, due to the release of adrenocorticoid and corticosterone hormones. Conclusion: More detailed studies are needed so that the real effects caused by the microorganisms that make up the intestinal microbiota on the functioning of the brain are elucidated in a clear and objective way.